Polymer composite with enhanced thermal conductivity and mechanical strength through orientation manipulating of BN. (26th May 2018) - Hu, Jiantao; Huang, Yun; Zeng, Xiaoliang; Li, Qiang; Ren, Linlin; Sun, Rong; Xu, Jian-Bin; Wong, Ching-Ping
Abstract: Herein, we report a fabrication of epoxy resin/oriented BN composites via a facile hot-pressing strategy. Benefitting from the force exerted vertically on the BN platelets, a well-ordered BN microstructure in the composites has been achieved, which renders the prepared composites an elevated thermal conductivity up to 6.09 W m −1 K −1 at 50 wt% loading, while it is only 2.44 W m −1 K −1 for epoxy resin/random BN composites. In addition, the composites show an enhanced tensile strength (31.79 MPa) and Young's modulus (4.63 GPa) when comparing with epoxy resin/random BN composites at the same 50 wt% loading (21.21 MPa and 1.48 GPa). We attribute the improved thermal conductivity to the well-aligned BN platelets in higher heat conduction direction based on the anisotropic thermal conduction ability of BN. The enhanced mechanical properties are ascribed to the increased friction area along the tensile in-plane direction and the decreased defects which are easily incorporated during the fabrication process. This study sheds a light for exploring future thermal management materials to meet the increasing heat dissipation demands. Graphical abstract: Image 1